Magnetically active pNIPAM nanosystems as temperature-sensitive biocompatible structures for controlled drug delivery - García-Pinel, Beatriz; Ortega Rodríguez, Alicia; Porras Alcalá, Cristina; Cabeza, Laura; Contreras-Cáceres, Rafael; Ortiz, Raúl; Díaz-Morilla, Amelia; Moscoso, Ana; Sarabia-García, Francisco Ramón; Prados, Jose; López-Romero, Juan Manuel; Melguizo, Consolación (Taylor and Francis, 2020)
Here, temperature-sensitive hybrid poly(N-isopropylacrylamide) (pNIPAM) nanosystems with magnetic response are synthesised and investigated for controlled release of 5-fluorouracil (5FU) and oxaliplatin (OXA). Initially, magnetic nanoparticles (@Fe3O4) are synthesised by co-precipitation approach and functionalised with acrylic acid (AA), 3-butenoic acid (3BA) or allylamine (AL) as comonomers. The thermo-responsive polymer is grown by free radical polymerisation using N-isopropylacrylamide (NIPAM) as monomer, N,N’-methylenbisacrylamide (BIS) as cross-linker, and 2,2’-azobis(2-methylpropionamidene) (V50) as initiator. We evaluate particle morphology by transmission electron microscopy (TEM) and particle size and surface charge by dynamic light scattering (DLS) and Z-potential (ZP) measurements. These magnetically active pNIPAM@ nanoformulations are loaded with 5-fluorouracil (5FU) and oxaliplatin (OXA) to determine loading efficiency, drug content and release as well as the cytotoxicity against T-84 colon cancer cells. Our results show high biocompatibility of pNIPAM nanoformulations using human blood cells and cultured cells. Interestingly, the pNIPAM@Fe3O4-3BA + 5FU nanoformulation significantly reduces the growth of T-84 cells (57% relative inhibition of proliferation). Indeed, pNIPAM-co-AL@Fe3O4-AA nanosystems produce a slight migration of HCT15 cells in suspension in the presence of an external magnetic field. Therefore, the obtained hybrid nanoparticles can be applied as a promising biocompatible nanoplatform for the delivery of 5FU and OXA in the improvement of colon cancer treatments.
Keywords: Química farmacéutica; 5-fluorouracil; pNIPAM nanosystems; Colon cancer; External magnetic field; Magnetic nanoparticles; Oxaliplatin